MORE THAN 2-YEARS FOLLOW-UP OF RESISTANT HYPERTENSIVE PATIENTS WITH NEUROVASCULAR DECOMPRESSION OF THE BRAIN STEM ON THE LEFT SIDE. (June 2018) - Fejes, I.; Voros, E.; Barzo, P.; Bajcsi, D.; Letoha, A.; Sonkodi, S.; Abraham, G.; Legrady, P.
Abstract : Objective: In the background of resistant hypertension (RHT) the neurovascular pulsatile compression (NVPC) of the left rostral ventrolateral medulla may play a role. In these cases a neurosurgical decompression (NVD) decreased the blood pressure (BP) and the antihypertensive medication became more effective. The aim of this work was to compare BP values recorded at the farthest time from the time of the NVD, up to maximum 31 December 2016. Design and method: Earlier we published first 2-year follow-up data of 9 operated patients. In this work we retrospectively collected these 9 patients data from the clinical center's patient management system. At the time of NVD the mean age, BMI and duration of HT were 43.7 ± 3.0 years, 28.5 ± 1.6 kg/m2 and 14.2 ± 3.1 years. We analyzed BP values recorded before NVD, 1 and 24 months after NVD and the last recorded ones. Results: The types of NVPC showed by the MR-angiography were confirmed by the NVD in all patients. The NVDs were performed between 2000 and 2004. The mean follow-up time was 11 years (minimum 3 years, maximum 16 years). Both the systolic and the diastolic BP decreased significantly in all cases after the NVD and at the last record they were significantly lower than before the NVD. Last recorded BP values compared to the 24-month data also were lower (148/96 mm Hg vs. 135/81 mm Hg). In 5 cases the number of antihypertensives increased and the mean number of combinations was higher compared to 24-month data (5.7 vs. 6.7). Conclusions: These results confirmed our previous opinion that in severe hypertension not responding to conventional therapy the NVD of the left side NVPC could guarantee a long-lasting BP reduction. Of course it could be not a direct effect of NVD but it may increase the sensitiveness for antihypertensive medication.